Strategi Pengembangan Agrowisata Desa Rantau Kermas Kabupaten Merangin dengan Metode SOAR - Hastuti, Dwi; Ningsih, Sri; Ayu, Putri (CV Global Research Publication, 2026)
This study aims to analyze and formulate the direction of agrotourism development in Merangin Regency using the SOAR (Strengths, Opportunities, Aspirations, Results) approach. The research method used is descriptive with a qualitative approach. Data were obtained through observation, interviews, documentation, and literature studies, then analyzed to identify strengths, opportunities, aspirations, and development results. The analysis results show that Merangin agrotourism has strengths in the form of abundant natural resource potential, beautiful landscapes, and local community support. Development opportunities are also quite large, supported by the increasing interest in nature-based tourism, government policies, and the development of digital technology. Based on the results of the SOAR calculation, the Strengths (9.3), Opportunities (9.4), Aspirations (9.45), and Results (9.42) scores were obtained. These values indicate that the aspirations and results aspects have the highest scores, indicating that the development of Merangin agrotourism has a clear strategic direction and targets. However, the strengths aspect still needs to be strengthened to be able to support the achievement of aspirations and results optimally. Thus, the development of Merangin agrotourism is directed at optimizing local potential, increasing human resource capacity, strengthening promotion, and sustainable management.